Localized corrosion behavior of a single-phase non-equimolar high entropy alloy. (20th May 2019) - Li, Tianshu; Swanson, Orion J.; Frankel, G.S.; Gerard, Angela Y.; Lu, Pin; Saal, James E.; Scully, J.R.
Abstract: In previous work, a design approach combining computational modeling and empirical knowledge has been reported to establish a more efficient paradigm for developing future corrosion resistant alloys. Using this approach, a single-phase non-equimolar high entropy alloy (HEA) was successfully designed and synthesized. In this work, a detailed experimental investigation of the localized corrosion behavior of this alloy is presented. The HEA was found to possess superior intrinsic pitting resistance and exhibit strong passivity, even in 6 M HCl. The ability of this HEA to initiate and propagate a pit has been studied. The pitting resistance was shown to result from the formation of a passive film with exceedingly strong resistance to breakdown and from a high resistance to pit propagation. Pitting was found to be significantly inhibited because of the extremely strong passivity, even in solutions with lower pH and higher chloride concentration than found in a typical local pit environment. The outstanding properties of the HEA validate the approach used for designing corrosion-resistant HEAs. Highlights: Computational designed single phase HEA with superior intrinsic pitting resistance. Designed HEA exhibits extremely strong passivity even in 6 M HCl. Passive film breakdown was significantly inhibited on designed HEA. Pit growth stability on HEA was greatly reduced due to an extremely small i diss, max .